POTENSI SPESIES DI SEKITAR MATA AIR BENA SEBAGAI INDIKATOR KETERSEDIAAN AIR DI DESA NIBAAF KABUPATEN TIMOR TENGAH UTARA - Metkono, Hesron; Binsasi, Remigius; Naisumu, Yolanda Getrudis (Jurusan Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Timor, 2024)
Nibaaf Village is one of the areas in Noemuti District, North Central Timor Regency. This village has a spring called Bena spring. Bena Spring is one of the natural springs located in the production forest area of ​​Nibaaf Village, North Central Timor Regency. This research aims to determine the type of vegetation, species that have potential as indicators of water availability, and the influence of vegetation on water availability, as well as to determine the efforts made by the Nibaaf Village community to protect and preserve Bena springs as a production forest area. This research was carried out from December 2023 to February 2024 at the Bena springs in Nibaaf Village, Noemuti District, North Central Timor Regency. The method used in this research is the quadratic plot method which is carried out by making 7 plots measuring 20 m x 20 m. The research results showed that there were 19 types of species distributed in tree growth forms, poles, saplings and seedlings. Consisting of 97 individuals for growth from trees, 70 individuals for growth from poles, 144 individuals for growth from saplings, and 430 individuals for growth from seedlings. The results of the highest INP data analysis for growth from trees were Eucaliptus alba with an INP of 181.27%. The highest INP for growth from poles is Swietenia mahagoni with an INP of 158.51%. The highest INP for growth from saplings is Syzgium aqueum with an INP of 242.08%. The highest INP for growth from seedlings was Sweitenia mahagoni with an INP of 64.17%. The Shannon Winner Diversity Index is in the medium category, the Evennes/Evenness Index is in the high category, and the Dominance Index is in the medium category. Types of plants that have potential as indicators of water availability around the Bena spring are Swietenia mahagoni, Syzygium aqueum, and Ficus benjamina. The existence of vegetation around the Bena spring has a big influence on water availability because it can conserve water. Therefore, this vegetation needs to be maintained and preserved or reforested in order to maintain the stability of water discharge during the dry season. Efforts made by the Nibaaf Village community to protect and preserve the Bena spring as a production forest area include: not cutting down trees carelessly, not throwing away rubbish, and carrying out reforestation to maintain soil fertility so that the spring does not dry out.